2014
DOI: 10.1530/eje-13-0694
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian function after allogeneic hematopoietic stem cell transplantation in childhood and adolescence

Abstract: Objective: The aim of the study was to evaluate long-term ovarian function after allogeneic hematopoietic stem cell transplantation (HSCT) in childhood and adolescence. Subjects and methods: Predictive factors for ovarian function were evaluated among 92 adult or pubertal female survivors transplanted at Huddinge and Helsinki University Hospital during 1978-2000, at a mean age of 9G4.3 years (range 1-19). At the time of the study a meanGS.D. of 13G5.5 years (range 6-27) had elapsed since the HSCT and the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 22 publications
(39 reference statements)
0
52
0
2
Order By: Relevance
“…Results were comparable in the cohorts of the European Group for Blood and Marrow Transplantation, the Center for International Blood and Marrow Transplant Research, and Vatanen and associates [8][9][10]. Recently, Borgmann-Staudt reported no births after TBI conditioning and only a single birth after chemotherapy conditioning among 85 women who had undergone allograft for leukemia or nonmalignant hemopathy as children and were 19 years or older at the time of follow-up [11].…”
Section: Introductionmentioning
confidence: 60%
“…Results were comparable in the cohorts of the European Group for Blood and Marrow Transplantation, the Center for International Blood and Marrow Transplant Research, and Vatanen and associates [8][9][10]. Recently, Borgmann-Staudt reported no births after TBI conditioning and only a single birth after chemotherapy conditioning among 85 women who had undergone allograft for leukemia or nonmalignant hemopathy as children and were 19 years or older at the time of follow-up [11].…”
Section: Introductionmentioning
confidence: 60%
“…Very long-term follow-up studies have shown that BuCy may be associated with normalization of HRQoL, no second malignancies in the absence of chronic graft-versus-host disease (cGVHD), and preservation of fertility in a significant number of patients transplanted prior to age 15 years. 10 The combination of 2 myeloablative alkylating agents such as Tt and busulfan or treosulfan may result in a very high infertility rate, 20,21 which is increasingly unacceptable in the new thalassemia era of effective chelation, where a substantial proportion of individuals with ST may bear children. 22 This study compares retrospectively 2 standard preparative regimens based on BuCy in addition to either Tt or ATG for matchedrelated low-risk BMTs for ST.…”
Section: Introductionmentioning
confidence: 99%
“…Yet explicit risk or protective factors for fertility recovery could not be defined and seem to vary between individuals. Vatanen et al have shown that females undergoing HSCT and CY conditioning regimen only, were more likely to experience spontaneous puberty and menarche and required HRT less often (Vatanen et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Recovery of fertility after HSCT therapy induced gonadal dysfunction has been reported in both sexes (Mertens et al 1998;Vatanen et al 2014;Rovo et al 2006). In males, the number of patients with spermatogenesis may rise with time (Rovo et al 2006).…”
Section: Introductionmentioning
confidence: 99%